HUBUNGAN KEBIASAAN MAKAN PAGI DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI SMP N 7 BUKITTINGGI - RAHMI, AULIA; Chair, Ira Meirina; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This study aimed to describe the breakfast habits of students, learning outcomes, and analyze the relationship between breakfast habits with student learning outcomes in mathematics. This research is correlational nature of survey research. The population in this study were all students of SMP N 7 Bukittinggi, amounting to 230 people. Samples numbered 70 people obtained by simple randoom sampling. Data processed by descriptive and correlation tests. Pimer data obtained in this study using questionnaires and secondary data obtained from the value before remedial student learning outcomes in mathematics. The results showed that by 34.29% students have a habit of having breakfast in the bad category.There 77% students acquire learning outcomes with values ​​below the number of completeness, and the rest 23% of students above the number of completeness. There is a significant relationship between breakfast habits with student learning outcomes in mathematics with a correlation coefficient of 0.481 with a significance value of 0.000. Keywords: habits, eating breakfast, learning outcomes